The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2024
DOI: 10.1021/jacs.3c10412
|View full text |Cite
|
Sign up to set email alerts
|

Dipolar Coupling as a Mechanism for Fine Control of Magnetic States in ErCOT-Alkyl Molecular Magnets

Maximilian G. Bernbeck,
Angelica P. Orlova,
Jeremy D. Hilgar
et al.

Abstract: The design of molecular magnets has progressed greatly by taking advantage of the ability to impart successive perturbations and control vibronic transitions in 4f n systems through the careful manipulation of the crystal field. Herein, we control the orientation and rigidity of two dinuclear ErCOT-based molecular magnets: the inversion-symmetric bridged [ErCOT(μ-Me)(THF)] 2 (2) and the nearly linear Li[(ErCOT) 2 (μ-Me) 3 ] (3). The conserved anisotropy of the ErCOT synthetic unit facilitates the direction of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 162 publications
0
4
0
Order By: Relevance
“…The nearly parallel alignment of the anisotropy axes of the ground doublets in 2-Er suggests the presence of ferromagnetic dipolar coupling between the ions, which is typically observed for two colinear axes that are also parallel to the interconnecting vector . However, ferromagnetic coupling is in stark contrast to the experimental χ M T ( T ) and M ( H ) data, clearly indicating antiferromagnetic interactions.…”
Section: Resultsmentioning
confidence: 81%
“…The nearly parallel alignment of the anisotropy axes of the ground doublets in 2-Er suggests the presence of ferromagnetic dipolar coupling between the ions, which is typically observed for two colinear axes that are also parallel to the interconnecting vector . However, ferromagnetic coupling is in stark contrast to the experimental χ M T ( T ) and M ( H ) data, clearly indicating antiferromagnetic interactions.…”
Section: Resultsmentioning
confidence: 81%
“…, barriers, relaxation, QTM, differ from their single ion characteristics drastically. Often, for polynuclear complexes their electronic properties can be enhanced when all metallic ions are anisotropic with parallel or nearly parallel arrangements of spins, 36,80–82 while for non-colinear arrangements it has been usually observed that the properties are diminished. 38,58,83 In contrast, the interaction of the three Dy( iii ) ions in [Dy 3 (hq) 7 (NO 3 ) 2 (H 2 O)] along with the canted spin arrangements, leads to a spin ground state with anisotropic characteristics and open loops and slow relaxation at zero field.…”
Section: Discussionmentioning
confidence: 99%
“…To further the development of favourable SMM properties and finally implement lanthanide-based molecules in devices, a detailed understanding of their magnetic properties continues to be a critical step. 28–31 A great deal of work has shed some light on the understanding of the magnetic behaviour of single lanthanide ion molecules, 32–38 denoting the importance of the role of magnetic interaction in SMMs. This understanding is required since polymetallic lanthanide clusters can show some unusual physical properties such as the observation of a toroidal magnetic 39–41 and strong magnetic exchange, causing an increment of the blocking temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…As such, the parameter of total magnetic interaction, −2.45 cm –1 , is very close to that determined by μ-SQUID, suggesting that a dominant dipolar coupling induces exchange biasing. From the spectrum of the low-lying exchange multiplets (Table S17), the energy gap between the lowest two exchanged KDs was determined to be 1.225 cm –1 , which is sufficient to suppress the QTM process …”
mentioning
confidence: 99%